Chordal rupture. II: comparison between repair and replacement. Issue 4 (October 1983) - Oliveira, D B; Dawkins, K D; Kay, P H; Paneth, M
Abstract : During the period 1970-81, 183 patients underwent mitral valve surgery for chordal rupture. Of these, 82 (45%) patients were treated by mitral valve repair and 101 (55%) by mitral valve replacement. Mean age at surgery was 57 years. The early mortality was nine of 183 (4.9%) patients, of whom five had undergone replacement and four repair. During the follow up period (mean 3.6 years, range 0.8-12.2 years) a further 27 patients died; 23 of these had undergone mitral valve replacement and four mitral valve repair. Cerebrovascular events accounted for 35% of the deaths after mitral valve replacement and none of those after mitral valve repair. In 11 patients repair was technically unsatisfactory, and mitral valve replacement was undertaken at the same operation; a further five patients required late replacement (mean 1.4 years) for pronounced mitral regurgitation. Actuarial curves predict a six year survival of 68 +/- 5.7% (mean +/- SD) for all patients after mitral valve replacement compared with 88 +/- 6.9% (mean +/- SD) after repair (p less than 0.01). Actuarial survival curves favour mitral valve repair as the procedure choice for chordal rupture, and in isolated posterior cusp repair breakdown of the repair is a rare occurrence.